If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (a + 3b)(2a + -5b) = 0 Multiply (a + 3b) * (2a + -5b) (a(2a + -5b) + 3b * (2a + -5b)) = 0 ((2a * a + -5b * a) + 3b * (2a + -5b)) = 0 Reorder the terms: ((-5ab + 2a2) + 3b * (2a + -5b)) = 0 ((-5ab + 2a2) + 3b * (2a + -5b)) = 0 (-5ab + 2a2 + (2a * 3b + -5b * 3b)) = 0 (-5ab + 2a2 + (6ab + -15b2)) = 0 Reorder the terms: (-5ab + 6ab + 2a2 + -15b2) = 0 Combine like terms: -5ab + 6ab = 1ab (1ab + 2a2 + -15b2) = 0 Solving 1ab + 2a2 + -15b2 = 0 Solving for variable 'a'. Factor a trinomial. (2a + -5b)(a + 3b) = 0Subproblem 1
Set the factor '(2a + -5b)' equal to zero and attempt to solve: Simplifying 2a + -5b = 0 Solving 2a + -5b = 0 Move all terms containing a to the left, all other terms to the right. Add '5b' to each side of the equation. 2a + -5b + 5b = 0 + 5b Combine like terms: -5b + 5b = 0 2a + 0 = 0 + 5b 2a = 0 + 5b Remove the zero: 2a = 5b Divide each side by '2'. a = 2.5b Simplifying a = 2.5bSubproblem 2
Set the factor '(a + 3b)' equal to zero and attempt to solve: Simplifying a + 3b = 0 Solving a + 3b = 0 Move all terms containing a to the left, all other terms to the right. Add '-3b' to each side of the equation. a + 3b + -3b = 0 + -3b Combine like terms: 3b + -3b = 0 a + 0 = 0 + -3b a = 0 + -3b Remove the zero: a = -3b Simplifying a = -3bSolution
a = {2.5b, -3b}
| 9m+30=33 | | 6x(6x-5)-3(5-6x)= | | x^2+23-39=0 | | 16z^4-81z^4=0 | | a^2+6a+36=0 | | 6+ln(x+5)=8 | | Xsquared+5cubed=9cubed | | 9x^4-16=10x^2-17 | | 8x-18=36-6x | | 3*(15-x)=18 | | 2(3x-1)=4 | | 3*(x-15)=18 | | 5(7m-3)=14(2m+5) | | 3*(x-15)=48 | | V=6(8x+2)(5x-4)-10(5x-4) | | (2y-1)dy=(3x^2+1)dx | | 4x=190 | | (2y-1)dy=(3x+1)dx | | 2ln(5x+1)=14 | | 12a-11=15a-10 | | 10z+4=1 | | 3(x+4)-12x=48 | | lnx=70.0173683 | | 2q+5y+4z=0 | | 8h-24=36 | | 12x-11=15x-10 | | 12=(n-1)(n-2)(n-3)(n-4)(n-5)-3n^2 | | -36=y-5y-21 | | 12=(n-1)(n-2)(n-3)(n-4)-(2n^3) | | 12=n^4-12n^3+35n^2-50n+24 | | 8+4x=7x | | -11-5X=-111 |